Pendidikan Multikultural Berbasis Khittah NU 1926: Dinamika Sosio-Keagamaan di Pondok Pesantren Nuhiyah Pambusuang - Mi'raj Mi'raj (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2025)
This study aims to examine the implementation of Khittah Nahdlatul Ulama (NU) 1926 values in multicultural education at Pondok Pesantren Nuhiyah Pambusuang, West Sulawesi. Amid the growing phenomena of religious intolerance and exclusivism, NU-affiliated pesantren hold a strategic position in fostering moderate Islamic values that align with the dynamics of a pluralistic society. Employing a qualitative approach with a phenomenological design, this study collected data through participatory observation, in-depth interviews, and documentation. The findings reveal that the core values of Khittah NU 1926 tawasuth (moderation), tasamuh (tolerance), tawazun (balance), and amar ma’ruf nahi munkar (ethical activism) have been systematically internalized through the pesantren’s curriculum, teaching methods, social interactions, and religious-social engagement. These values are not merely taught as normative doctrines but are embodied in the students’ daily contextual and practical experiences. The study concludes that an educational model grounded in Khittah NU fosters inclusive, reflective, and resilient student character capable of responding to the challenges of pluralism, social transformation, and the demands of a civil global society.